2018
DOI: 10.1111/jfb.13681
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with oregano essential oil on prevention of the ectoparasitic protozoans Ichthyobodo salmonis and Trichodina truttae in juvenile chum salmon Oncorhynchus keta

Abstract: The present study performed three experiments to establish a practical prevention strategy for the ectoparasitic flagellate Ichthyobodo salmonis and ciliate Trichodina truttae in hatchery-reared juvenile chum salmon Oncorhynchus keta using dietary supplementation with oregano essential oil. Experiment 1 showed that a diet supplemented for 3 weeks with 0.02% oregano essential oil significantly prevented infection with I. salmonis and T. truttae in juveniles reared in small tanks. Experiment 2, in outdoor hatche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…damselae of four EOs ( Origanum vulgare , Eucalyptus globulus , Melaleuca alternifolia and Lavandula angustifolia ) was evaluated by Gholipourkanani and coworkers All treatments showed antibacterial activity, and in almost all cases, the activity of the nano‐emulsions was superior to their essential oil counterparts. Origanum essential oil had a pronounced influence on the innate immunity and increased the Tilapia zillii resistance to Vibrio anguillarum and dietary supplementation with 0.02 % oregano essential oil is a practical prevention strategy for Ichthyobodo salmonis and Trichodina truttae infection in Oncorhynchus keta . Finally, a relevant and promising study on the efficacy of several EOs against Pseudomonas spp.…”
Section: Essential Oils: Very Old ‘Guys’ With Great Prospectsmentioning
confidence: 60%
See 1 more Smart Citation
“…damselae of four EOs ( Origanum vulgare , Eucalyptus globulus , Melaleuca alternifolia and Lavandula angustifolia ) was evaluated by Gholipourkanani and coworkers All treatments showed antibacterial activity, and in almost all cases, the activity of the nano‐emulsions was superior to their essential oil counterparts. Origanum essential oil had a pronounced influence on the innate immunity and increased the Tilapia zillii resistance to Vibrio anguillarum and dietary supplementation with 0.02 % oregano essential oil is a practical prevention strategy for Ichthyobodo salmonis and Trichodina truttae infection in Oncorhynchus keta . Finally, a relevant and promising study on the efficacy of several EOs against Pseudomonas spp.…”
Section: Essential Oils: Very Old ‘Guys’ With Great Prospectsmentioning
confidence: 60%
“…Origanum essential oil had a pronounced influence on the innate immunity and increased the Tilapia zillii resistance to Vibrio anguillarum [267] and dietary supplementation with 0.02 % oregano essential oil is a practical prevention strategy for Ichthyobodo salmonis and Trichodina truttae infection in Oncorhynchus keta. [268] Finally, a relevant and promising study on the efficacy of several EOs against Pseudomonas spp. isolated from fish was conducted by Kačániová et al, [269] suggesting that the EO may be used as natural compounds with antipseudomonal activity to improve the microbiological quality of freshly caught freshwater fish.…”
Section: Diet Supplement For Animal Feeding and Application For Animamentioning
confidence: 99%
“…This study confirmed the efficacy of garlic towards amoebae at a concentration of 16.9 mg/ml. As oregano essential oil has been shown to be effective in prevention of infection with Ichthyobodo and Trichodina in Oncorhynchus keta (Mizuno et al, 2018), we also tested oregano and found it to be effective in killing amoebae at a concentration of 17.9 mg/ml and partly effective at a concentration of 8.9 mg/ml. The bacterial lipopeptide surfactant H6 was previously shown effective against theronts of the ciliate Ichthyophthirius (Al‐Jubury et al, 2018), and it was lethal to Vannella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Herbal constituents including crude extract of garlic ( Allium sativum ) and/or Origanum vulgare eliminated Trichodina sp. from tilapia ( Oreochromis niloticus ) (Chitmanat, Tongdonmuan, & Nunsong, 2005), from European eel ( Anguilla anguilla ) (Madsen, Buchmann, & Mellergaard, 2000), Ichthyophthirius multifiliis from rainbow trout ( O. mykiss ) (Buchmann, Jensen, & Kruse, 2003) and Ichthyobodo and Trichodina from Oncorhynchus keta (Mizuno et al, 2018). In addition, a bacterial lipopeptide, a biosurfactant isolated from Pseudomonas (strain H6), is able to kill the oomycete Saprolegnia diclina infecting fish eggs (Liu et al, 2015) as well as three life cycle stages of the pathogenic ciliate Ichthyophthirius multifiliis (Al‐Jubury et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Developing therapeutic programmes that are effective and do not have a deleterious influence on the aquatic environment is often difficult. Dietary supplementation with oregano essential oil reduced infection rate of two common ectoparasites of chum salmon Oncorhynchus keta (Walbaum 1792) in Japan, improved growth in freshwater and resulted in higher survival rates following transfer to seawater (Mizuno et al ., ).…”
mentioning
confidence: 99%